Efektivitas Program Asimilasi Warga Binaan Pemasyarakatan Terhadap Kesiapan Integrasi Narapidana ke Masyarakat (Studi pada Lembaga Pemasyarakatan Klas IIA Padang) - Monsosilo Monsosilo (Legalitas: Jurnal Hukum, 2021)
The purposes of these researches are prisoners to society in the penitentiary of Klas IIA Padang and the obstacles faced in the assimilation program of prisoner to society in the penitentiary of Klas IIA Padang? Third, how is the effective of assimilation program in the preparation of integration of prisoners to society in the penitentiary of Klas IIA Padang. The specification of the research is descriptive analytic. The method uses is the normative and juridical empiric method. From the research results obtained several conclusions: First, the effectiveness of assimilation in the preparation of integration of prisoners to society in the penitentiary of Klas IIA Padang is well and suitable with the law regulation. it is reflected by penitentiary by giving guidance and establishment of prisoner. Second, the obstacles faced in the assimilation program of prisoner to society in the penitentiary of Klas IIA Padang are internal and external obstacles. The internal consist of (a) lack of fund; (b) no expert who has experience; (c) no cooperation to third person. Whereas, the external obstacles are: (a) infectivity of law regulation; (b) the bad society views to the prisoners; and (c) long process to get permission. The efforts to solve the problems are: (a) Looking of alternative to strength law procedural; (b) adding fund and selling product; (c) preparation of alternative expert; (d) cooperate with outside; (e) adding of fund; (f) looking alternative and selling product; and (g) doing social activities.